Pengaruh Budaya Organisasi, Dukungan Sosial, dan Strategi Coping terhadap Kesehatan Mental Mahasiswa: Analisis Regresi pada Anggota Himpunan Mahasiswa Universitas Muhammadiyah Bandung - Ayesa Aulia Sofwa; Sanita Putri Yaperta; Siska Amelia; Sofa Parihah Nurasiah (Indo Publishing, 2026)
Student organizations provide a strategic space for leadership development, yet an unhealthy organizational culture can become a source of psychological pressure for its members. This study examines the influence of organizational culture, social support, and coping strategies on the mental health of active members of student associations (himpunan mahasiswa) at Universitas Muhammadiyah Bandung, using a quantitative regression approach. An explanatory survey design guided the study, with active members recruited through proportionate stratified random sampling and a minimum sample size determined by the Slovin formula. Data were collected using a twenty-item Likert-scale questionnaire and analyzed through multiple linear regression following validity, reliability, and classical assumption testing. Owing to a response rate below the calculated minimum sample, the findings are presented descriptively and interpreted as preliminary evidence rather than a fully validated regression model. The results indicate that a supportive organizational culture, marked by strong communal values and low hierarchical pressure, is descriptively associated with better emotional regulation and self-care among members, while ambiguity in task division corresponds with a lower tendency to seek collective problem-solving. These findings contribute empirical insight toward building healthier and more supportive organizational climates in higher education and provide a foundation for future confirmatory research with a larger sample.